Long-Term Antithyroid Drug Therapy in Smoldering or Fluctuating-Type Graves’ Hyperthyroidism with Potassium Iodide - Ken Okamura (Endocrinology and Metabolism)
Graves’ hyperthyroidism is characterized by stimulation of the thyroid gland by thyroid-stimulating hormone receptor antibodies (TRAbs). Antithyroid drug (ATD) continuation is recommended as long as the thyroid gland is stimulated. Goiter size, thyroidal 123I uptake, serum thyroglobulin level, and TRAb positivity are reliable markers of thyroid stimulation. Attention must also be paid to the responsiveness of the thyroid gland due to the high prevalence of painless thyroiditis and spontaneous hypothyroidism during treatment. TRAbs disappeared at <5 years entering remission in 36.6% of patients (smooth-type), while re-elevation of TRAb activity occurred in 37.7% (fluctuating-type) and remained positive for >5 years in 21.1% (smoldering-type). Seven percent of patients remained positive for TRAbs for >30 years, requiring life-long ATD treatment. Remission occurred after median 6.8 years (interquartile range, 4.0 to 10.9) of ATD treatment in 55% of patients. However, late relapse may occur after stressful events (dormant type). In apparently intractable Graves’ disease (GD) with a large goiter (>40 g), 131I therapy should be considered. For initial and long-term ATD treatment, we must choose effective, safe, and economical drugs such as 100 mg potassium iodide (KI), although KI sensitivity varies in patients with GD. Thionamide, which has notorious side effects, is added only during the KI-resistant period.